Peningkatan Hasil Belajar Pai Dengan Media Microsoft Teams Dan Form Office 365 Siswa Kelas VII B SMP Negeri 5 Surabaya - Eny Nilawati; Ach. Khusnan; Barudin (Jurnal Pendidikan Agama Islam Miazhar, 2022)
This research is motivated by the fact that during the pandemic the learning outcomes of PAI students at SMP Negeri 5 Surabaya were still relatively low. Therefore, teachers are expected to improve student learning outcomes. Learning media that allows it to affect student learning outcomes is by using Microsoft Teams media and Form Office 365. Both of these media are online learning media and evaluate learning online as well. The question to be answered is whether the application of Microsoft Teams media and Office 365 Forms can improve learning outcomes for PAI subjects at SMP Negeri 5 Surabaya for the 2022/2023 academic year. This research was conducted to improve the learning outcomes of class VII B students of SMP Negeri 5 Surabaya. This study uses a Classroom Action Research (CAR) approach. PTK consists of 3 cycles, each cycle consisting of planning, implementing, observing, and reflecting. From this study it shows that the use of Microsoft Teams media and Office 365 Forms can improve student learning outcomes with the following results: cycle I the percentage of learning achievement there are 16 students or 51.61% of students who complete, while there are 15 students or 48.39 % of students who did not complete. In Cycle II, the percentage of learning achievement was 24 students or 77.42% of students who completed, while there were 7 students or 22.58% of students who did not complete. In Cycle III, the percentage of learning achievement was 29 students or 93.55% of students who completed, while there were 2 students or 6.45% of students who did not complete, this PTK was declared successful.